PELATIHAN PEMULASARAAN JENAZAH SEBAGAI UPAYA TRANSFORMASI PENGETAHUAN KEAGAMAAN BAGI IBU-IBU MUSLIMAT DESA SIDOMULYO KEDIRI - thoriq, thoriqul; Agustin, Dinar Ayu Chandra; Hakim, Wilda Rochman; Syayekti, Ela Indah Dwi; Hanifah, Farah; Yasmin, Zahra; Abdullah, Muhammad Ilham; Samawati, Astin Nurhidayah; Prayogo, Galih; Ningtyas, Lailatun Nuriyatin; Agustina, Aldila Aliffia Is Sya; Witanti , Wahyu; Yurista, Karisma; Wulandari, Putri; Muhandis, Alivi; Sabila, Zhafira Nauva; Murendra, Eldico Oktaveri; Nuruddin, Beta Afkarul Wafiroh; Alifia, Aqsagya Putri (Abdimas IAI Ngawi, 2025)
This community service activity aims to empower Muslimat women in Sidomulyo Village, Semen District, Kediri Regency, through training in funeral arrangements in accordance with Islamic law. The main issue raised is the low understanding and skills of the community, especially women, in taking care of corpses appropriately and according to religious guidance. The training was designed using the Participatory Action Research (PAR) approach, which involves active participation of the community in all stages: problem identification, planning, implementation, and evaluation. The training materials included procedures for bathing, shrouding, praying and burying the dead, which were delivered theoretically and practically by competent resource persons. The results of the training showed a significant increase in participants' knowledge and skills, as well as encouraging social change in the form of growing collective awareness of the importance of women's independence in the management of corpses in rural environments. This activity is expected to be a sustainable training model that can be replicated in other areas with similar problems. Keywords: Women's Empowerment, Funeral Management, Muslimat, Community Service, Participatory Action Research   Abstrak: Kegiatan pengabdian masyarakat ini bertujuan untuk memberdayakan ibu-ibu Muslimat Desa Sidomulyo, Kecamatan Semen, Kabupaten Kediri, melalui pelatihan pemulasaraan jenazah yang sesuai dengan syariat Islam. Isu utama yang diangkat adalah rendahnya pemahaman dan keterampilan masyarakat, khususnya perempuan, dalam mengurus jenazah secara tepat dan sesuai tuntunan agama. Pelatihan ini dirancang menggunakan pendekatan Participatory Action Research (PAR), yang melibatkan partisipasi aktif masyarakat dalam seluruh tahapan: identifikasi masalah, perencanaan, pelaksanaan, hingga evaluasi. Materi pelatihan meliputi tata cara memandikan, mengkafani, menshalatkan, dan menguburkan jenazah, yang disampaikan secara teoritis dan praktis oleh narasumber kompeten. Hasil pelatihan menunjukkan peningkatan signifikan dalam pengetahuan dan keterampilan peserta, serta mendorong perubahan sosial berupa tumbuhnya kesadaran kolektif akan pentingnya kemandirian perempuan dalam pengurusan jenazah di lingkungan pedesaan. Kegiatan ini diharapkan menjadi model pelatihan berkelanjutan yang dapat direplikasi di wilayah lain dengan permasalahan serupa. Kata Kunci: Pemberdayaan Perempuan, Pemulasaraan Jenazah, Muslimat, Pengabdian Masyarakat, Participatory Action Research